Ethics of human research in Peru. Yet another pending task. - Casado, Fanny L. (2021)
We are currently cruising through a second wave of cases during the pandemics of COVID-19 in Peru. Anonymous heroes leave their houses every day and keep offering their work to support their families and communities. After almost a year of the beginning of this Public Health Crisis, much more is being demanded from health and allied professionals. Important efforts leading to improvements on infrastructure and technical guidance for medical innovations have been forced to move forward and be implemented in unprecedented timelines, but their visibility is hindered by another pending task in the Peruvian Health System related to the Ethics of Human Research.